2011
DOI: 10.1520/gtj103095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sample Size on the Behavior of Granular Materials

Abstract: International audienceNatural soils or coarse granular materials containing large particles such as rockfill or ballast are often an issue for geotechnical projects. However, since it is usually complicated or impossible to set up a big enough experimental apparatus to test these materials, their mechanical behavior remains poorly known.To circumvent this difficulty, we have developed a set of triaxial cells of various sizes to study the experimental behavior of granular soils containing particle sizes of up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…We select 1D loading for simplicity of the experimental setup, for the relative ease of reaching stress levels greater than 1 MPa and because the cylindrical specimen shapes are convenient for X-ray tomography. In order to minimise scale effects, (see, for example, Hu et al [11]), the sample diameter is chosen such that the sample diameter is considerably larger than the mean grain size . The sample is prepared with a zero drop height, and the top surface is compacted with the loading ram in order to assure a horizontal surface.…”
Section: Methodsmentioning
confidence: 99%
“…We select 1D loading for simplicity of the experimental setup, for the relative ease of reaching stress levels greater than 1 MPa and because the cylindrical specimen shapes are convenient for X-ray tomography. In order to minimise scale effects, (see, for example, Hu et al [11]), the sample diameter is chosen such that the sample diameter is considerably larger than the mean grain size . The sample is prepared with a zero drop height, and the top surface is compacted with the loading ram in order to assure a horizontal surface.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, several researchers have experimentally demonstrated that yield locus and stress-strain responses interpreted from the conventional triaxial tests were noticeably dependent on the sample scale. [15][16][17][18] When shearing takes place in the conventional triaxial test, soil specimen often deviates from homogeneity to inhomogeneity. The transition from an equilibrium state toward another mechanical state is accompanied by the development of kinetic energy.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Gupta et al [10], Li et al [11], and Kim et al [12] support that the internal friction angle ϕ increases with the improvement of d max . On the contrary, Lee [13] and Hu et al [14] believe that the maximum particle size d max has little effect on the peak internal friction angle ϕ. Xu et al [15], Wei et al [16], and Simoni et al [17] found that the internal friction angle increases with the reduction of content of fine particles, and Li et al [18] observed that when the fine particle content is relatively low, the internal friction angle is stable at a certain level; however, after that, it decreases rapidly with increasing fine-particle content.…”
Section: Introductionmentioning
confidence: 99%